An Analysis on Interlanguage Fossilization in Students’ Writing Performance - Nurul Aini; M. Khoirul Mufid; Eny Maulita Purnama Sari (Center of Language and Cultural Studies [CLCS], 2020)
This present study tries to investigate the students’ writing performance to know whether interlanguage fossilization is occurring or not. The primary goal of this research is to give information relating to interlanguage fossilization in students’ writing performance of the English Education Study Program of IAIN JuraiSiwo Metro. This research is qualitative research. It is used to describe interlanguage fossilization that occurred in students’ writing performance. The writer uses observation, documentation, and interview to collect the data. Purposive sampling is the technique for choosing the ten students of the sixth and the eight-semester of English Education Study Program of IAIN JuraiSiwo Metro in the Academic Year of 2017/2018. The result of this research shows that there are two types of interlanguage fossilization that are commonly produced by students’ writing performance. They are syntactical fossilization and morphological fossilization. Syntactical fossilization consists of 71,86% and morphological fossilization consists of 28,14%. Moreover, the interlanguage fossilization phenomenon in students’ writing performance is caused by the students’ low English proficiency. Therefore, students should be more active to improve their English ability.